Suspended sediment properties in the Lower Mekong River, from fluvial to estuarine environments. (5th February 2020) - Le, Hoang-Anh; Gratiot, Nicolas; Santini, William; Ribolzi, Olivier; Tran, Duc; Meriaux, Xavier; Deleersnijder, Eric; Soares-Frazão, Sandra
Abstract: The Mekong river is one of the largest rivers in the world, which flows through six countries of Southeast Asia (China, Myanmar, Laos, Thailand, Cambodia and Vietnam). Its hydro-sedimentary regime is changing rapidly, as a consequence of a regional shift of land use (agriculture, road, etc.), damming, sand mining and climate changes, among others. This study assesses the behavior of particles transported in suspension in the Lower Mekong River (LMR), along approximately 1700 km from fluvial to estuarine environments. Suspended sediment properties were estimated, simultaneously with hydrodynamic conditions, during three field campaigns. In addition, further investigations were performed in the laboratory to assess the structures of particles (flocculated or not), their capacity to flocculate (and the impacts on siltation), under a wide range of sediment concentration (20–30, 000 mg.L −1 ). This study confirms that suspended sediment transported in the LMR are predominantly (75% by volume) flocculi (or freshly eroded soils aggregates), with median aggregated particle size in the range 10–20 μm and median settling velocity of the order of 0.01–0.1 mm s −1 . These flocculi are robust under the hydrodynamic conditions (turbulence and suspended sediment concentration – SSC) existing in the LMR. Laboratory investigations reveal the existence of a threshold sediment concentration (400 mg.L −1 ), beyond which flocculation and sedimentation increase of orders of magnitudes. Thus, concentration that exceeds this threshold might promote the formation of so-called fluid mud layers. Because of the nonlinear response of flocculation and sedimentation with SSC and considering the ongoing changes at a regional scale in the LMR, higher occurrence of fluid mud layers in the fluvial upstream waterbodies might be anticipated, and a lower occurrence in estuaries and alongshore where the concentration decrease. The geomorphology could be impacted, with an over-siltation in dams and an exacerbated erosion of the muddy-mangrove coast. Highlights: More than 75% of particles transported in suspension in the Lower Mekong River are flocculated. Flocculi's population (10–20 μm) predominates and are stable structures. The regular formation of fluid mud layers (55 - 60 % of occurrence) strongly participates to the geomorphological evolution.